Phylogenetic Evidence that Two Submerged-Habitat Fungal Species, Speiropsis pedatospora and Xylomyces chlamydosporus, Belong to the Order Jahnulales Insertae Sedis Dothideomycetes - RIRY PRIHATINI; NATTAWUT BOONYUEN; SOMSAK SIVICHAI (Microbiology Indonesia, 2008)
The genera Speiropsis and Xylomyces are anomorph fungi. The taxonomic address for the fungi has been unclear. In this study, observation of morphological traits indicates that they have a unique pattern of mycelia with dark-brown to black colour and thick-walled hyphae. The same culture patterns of certain fungi isolated from freshwater habitats in Thailand were selected from BIOTEC Culture Collection (BCC, Thailand), while more species were added from Centraalbureau voor Schimmelcultures (CBS, Netherlands). These fungi were composed of Jahnula spp. (2-celled ascospores), Brachiosphaera tropicalis (hyaline and 4-5 armed conidia), S. pedatospora (hyaline and branches conidia) and Xylomyces sp. (dematiaceous and fusiform chlamydospores). This study was undertaken to confirm the taxonomic address for S. pedatospora and Xylomyces based on phylogenetics relationships as inferred from their ITS rDNA sequence data by using MP (unweighted and successive weighted MP), NJ, ML and Bayesian analysis. Phylogenic analysis revealed that isolates of S. pedatospora (2 strains) was a member of the Order Jahnulales and clustered with Jahnula spp. (5 strains) and B. tropicalis (4 strains) with >82% bootstrap support and 100% posterior probabilities. Four isolates of X. chlamydosporus, X. elegans and X. aquaticus were shown to be polyphyletic within the Jahnulales and Pleoporales. The MP and NJ showed the same topology as in the Jahnulales clade obtained by ML analysis.